Sex differences in the natural history of plaque progression by serial coronary computed tomography angiography. (25th November 2020) - El Mahdiui, M; Smit, J.M; Van Rosendael, A.R; Neglia, D; Knuuti, J; Buechel, R.R; Teresinska, A; Pizzi, M.N; Poddighe, R; Mertens, B.J; Caselli, C; Rocchiccioli, S; et al.
Abstract: Background: Sex related differences exist for coronary artery disease (CAD). Women tend to be older when presenting with CAD and have lower rates of obstructive disease. Invasive intravascular ultrasound studies have shown differences in plaque composition between males and females. However, these studies were performed in a high risk population needing invasive imaging. Coronary computed tomography angiography (CTA) allows for a fast and non-invasive quantification of CAD in low risk patients. Sex differences and quantitative analysis of plaque progression and changes in plaque composition have not been studied intensively. Purpose: To evaluate the role of sex on long term plaque progression and on the change of plaque composition in a population with low-intermediate risk. Methods: Patients that received a coronary CTA were prospectively included in the SMARTool study to receive a follow-up coronary CTA. In total, 275 patients from 5 European countries were recruited in 7 centers. Baseline and follow-up coronary CTA were quantitative analyzed on a per-lesion basis using dedicated software package. Patients without coronary plaques at follow-up or with uninterpretable coronary CTA results were excluded. Total plaque volume and compositional volumes, calcified or non-calcified (defined as fibrous, fibro-fatty or necrotic core), were normalized using the vessel volume to calculate a percentage atheroma volume (PAV). Lesions between males and females were compared using linear mixed models. We further classified patients into age groups <55 and ≥55 years to evaluate the influence of menopause on plaque progression. Results: In total, 211 patients were included in this analysis, 146 (69%) were male and 65 (31%) were female. Mean interscan period was 6.2±1.4 years. Females were older (64±7 vs 61±8 years; p<0.001), had higher HDL levels (56±15 vs 49±15 mg/dL; p=0.003) and presented more often with atypical chest pain (62 vs 38%; p=0.017). Males had 434 plaque sites and females 156. On a per-lesion analysis females had less fibro-fatty PAV compared to males (β −1.3±0.4%; p<0.001), no other differences were seen (p>0.05). When stratifying the patients in above and below 55 years old, females still had less fibro-fatty PAV compared to males in both age groups (p<0.05). However, females in the age group <55 years showed more regression of fibrous PAV compared to males (β −0.8±0.3% per year; p=0.002) and non-calcified plaque PAV (β −0.7±0.3% per year; p=0.027) (Figure). Conclusions: Males have larger fibro-fatty PAV compared to females, however the rate of change did not differ. Younger women showed more regression of fibrous PAV and non-calcified PAV compared to males. No differences in the rate of plaque progression or plaque composition changes were seen between males and females in the older age group. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): EU H2020 research and innovation program